The Role of the Spirit (rûaḥ) in the Ministry of the Prophet Ezekiel - Igbo, Philip (Journal of religion and human relations, 2020)
The role of the rûah Yhwh is emphasized in the Old Testament. The rûah is often regarded as Yhwh’s agent in the accomplishment his purpose. Often in the Old Testament, the rûah is said to seize or enter into or fall upon a person. The rûah falling on a person refers to the general empowerment of that person to perform a given task. The rûaḥ plays an active role in the prophet’s ministry. When it is said that the Spirit of God seized or entered a prophet, it means that he is empowered for his prophetic ministry. The role of the Spirit is particularly pronounced in the ministry of the prophet Ezekiel. Ezekiel is often portrayed as a man seized by the in the Spirit of the Lord. The rûaḥ seizing the prophet or entering him (Ezek 2:2) or falling upon him (Ezek 3:24), refers to the power of God at work in him, revealing to him what he is to say (Ezek 11:5)and enabled him to obediently fulfill his commission.